Participatory Democracy, Science and Technology - Rogers, K. author. aut Link
IX, 252 p.
Keywords: Taking insights from the philosophy of science and technology, theories of participatory democracy and Critical Theory, the author tackles and explores how democratic participation in scientific research and technological innovation could be possible, as a deliberative means of improving the rational basis for the development of modern society.